KUALITAS PELAYANAN DINAS PERHUBUNGAN KOTA MAKASSAR - A. M. Fadly Mappisabbi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2022)
This study aims to determine the inhibiting factors on service quality in the Development, Safety, and Enforcement (PKP) at the Makassar City Transportation Service. The type of research used in this study was qualitative descriptive data using quantitative data. The research findings are that there are several factors that become obstacles in the quality of Services for Development, Safety and Enforcement (PKP) at the Makassar City Transportation Service, including; Law Enforcers or Officers have not been alert in carrying out services, public awareness is still low, and facilities and infrastructure are not yet adequate.